Pattern of Poisoning in Isfahan - Gholamreza Masoumi; Nastaran Eizadi-Mood; Mojtaba Akabri; Ayatolah Sohrabi; Yusef Khalili (مجله دانشکده پزشکی اصفهان, 2012)
Background: Poisoning is an important medical emergency. The purpose of this study was to portray the pattern of poisoning in Isfahan, Iran. Methods: This cross-sectional study included all patients (n = 402) with acute poisoning who attended the Emergency Department of Noor and Ali-Asghar hospitals in Isfahan, Iran, during 2008. The variables such as age, sex, residential location, educational level, type and cause of poisoning were reviewed and analyzed. Findings: The mean age of the cases was 26.5 ± 11.6 years and 54.7% of the patients were male. The majority of cases (92.8%) lived in urban areas. The main agent of poisoning was drugs and the most frequently involved drug groups were psychological drugs (33.8%). The most overall common route of exposure was ingestion (93.3%). The mortality rate was 2% while 91.3% were admitted due to suicidal attempts. No significant differences were observed in age, sex distribution, poisoning outcome or types between suicidal patients and others. However, the history of psychiatric diseases (P < 0.0001) and addiction (P = 0.02) were significantly more prevalent among suicidal patients. Conclusion: Attempted suicide was the most common route of poisoning which necessitates attention to the risk factors and prognostic factors of poisoning.